Exploring the Depths of the Psyche: The Id, Ego, and Superego in Jerry Spinelli's Stargirl - Berliana, Charoline Rose (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
ABSTRACT: In the context of psychoanalytic theory, the structure of human personality consists of three main parts: the Id, the Ego, and the Superego. The Id is the unconscious part driven by instincts and basic needs, the Ego tries to satisfy the basic needs of the Id realistically and according to the norms instilled by the Superego, and the Superego which is the socially accepted moral aspect. The purpose of this study is to explain and describe the forms of Id, Ego, and Superego in the narrator and main character in the novel Stargirl by Jerry Spinelli. The method used in this study is a descriptive method with a qualitative approach. The theory used is Sigmund Freud's psychoanalysis theory with a Literary Psychology approach. The result of this study is that Id is more dominant in Stargirl, Ego and Superego is more dominant in Leo. The discussion of this research is that Stargirl's Id is described as something that is difficult to understand and difficult to hold. Leo's ego is described as reflecting an attempt to find a balance between individual desires and the demands of social normal, Leo's superego wants to show society the true name Stargirl. In conclusion, Stargirl novels depict the complex dynamics between id, ego, and superego in shaping characters and influencing their actions.   Keywords: Psyche, Psychology, Psychoanalysis, Id, Ego, Superego